An annotated checklist of flora of Drass valley (Ladakh), India - Banoo, Sakina; Ganie, Aijaz Hassan; Khuroo, Anzar Ahmad (Phytotaxa, 2025)
In this study, an annotated checklist of the flora of Drass valley, located in the Trans-Himalaya region of Ladakh, is presented. The checklist is based on extensive field explorations conducted from 2019–2022, and records 518 species belonging to 286 genera and 66 families from the study area. These include 464 dicot, 48 monocot, and 6 gymnosperm species. Asteraceae contributed the highest number of 78 species, followed by Fabaceae (32 spp.) and Brassicaceae (31 spp.). Astragalus was the dominant genera with 13 species, followed by Potentilla (10 spp.) and Corydalis (9 spp.). Herbs were the most prevalent growthform (442 spp., 85.33%), followed by subshrubs (33 spp., 6.37%), shrubs (26 spp., 5.02%), trees (15 spp., 2.9%) and climbers with only two species (0.39%). Perennials were predominant contributing 390 species, followed by annuals (98 spp.) and biennials (30 spp.). Habitat-wise, the steppe grasslands harbour the highest number of 183 species, followed by agri-fields (151 spp.), and alpine meadows (138 spp.). Our results reveal that this coldspot, comprising just 0.25% area of the entire Ladakh, harbours about half of the total floristic diversity known from this Trans-Himalayan region. Looking ahead, the present study will form scientific baseline for undertaking advanced research studies in the region, and guide formulation of policy and management strategies towards conservation and sustainable use of the plant resources in this second coldest human-inhabited area of the world.